Comparação do padrão inflamatório intestinal crônico antígeno específico entre camundongos C57BL/6J e BALB/C - Castro Junior, Archimedes Barbosa de (2006)
Food allergy is an adverse immunological reaction that occurs in sensitized individuals after ingesting the antigenic food. The reactions that take place in the intestine are considered to be a type of inflammatory bowel disease and may be a consequence of tolerance rupture to food antigens leading to uncontrolled immune responses. The majority of murine models of food allergy are due to T helper 2 like immune responses, with IgE production and immediate inflammatory reactions. But allergies can also be induced in the absence of IgE, with a T helper 1 response. This discrepancy seems to be due to many factors such as genetic differences, timing of food intake and others. Our objective in this work is to compare the immune responses of two different murine inbred strains C57BL/6J and BALB/c using an antigen-specific inflammatory bowel disease model induced by peanut sensitization. Female mice of both strains were divided into normal or immune groups. Immune animals received a first subcutaneous immunization with 100ug of peanut protein extract with 1mg alum and a booster immunization only with the protein extract. Normal animals were sham immunized twice. After the second immunization the animals were subdivided in 4 groups and challenged with a diet-containing peanut for two, three or four weeks and the last group (control animals) were maintained with conventional chow. We analyzed antipeanut total IgG and IgG1 titers, the histological pattern of duodenal mucosa, the intestinal epithelial cell/intraepithelial leukocytes ratio (IEC/IEL) of duodenal villi and the CD4+ and CD8+ T cell patterns in Peyer patches and mesenteric lymph nodes of these animals. Our results show that BALB/c immune mice presented higher titers of antipeanut total IgG, but not IgG1, when compared to immune mice from C57BL/6J strain. BALB/c, but not C57BL/6J, normal mice presented increasing antipeanut IgG and IgG1 titers after eating peanuts without important changes in the mucosa. Two weeks of challenge diet was sufficient to induce an increase of intraepithelial leukocytes numbers (drop in IEC/IEL ratio) of BALB/c immune animals while in C57BL/6J mice this feature only takes place after the 3rd 4th week of challenge. BALB/c immune animals presented other intestinal inflammatory parameters, such as, edema, loss of villi integrity, which were more intense than in C57BL/6J immune mice after the 2nd week of challenge. After two weeks of peanut exposition, C57BL/6J immune animals presented an arise of CD8+ T cell population in Peyer patches while in mesenteric lymph nodes CD8+ T cell number decreased. Interestingly, C57BL/6J normal mice presented an increased number of CD4+ T cells in mesenteric lymph nodes after two weeks of being exposed to peanut for the first time. We concluded that there are differences in the intestinal inflammatory patterns between C57BL/6J and BALB/c strains. BALB/c strain is more susceptible to the acute reactions of the intestinal inflammation and the triggering of inflammatory signals is quicker and more intense in these mice. The higher titers of IgGs observed in BALB/c normal mice that eat peanuts could be explained by an active process of oral tolerization and not oral sensitization to this seed and that this phenomenon is characteristic of BALB/c strain. We also conclude that, at least in C57BL/6J strain, the probable T cell type, which is responsible for the mucosa damage in immune animals in our model of inflammatory bowel disease, are the CD8+ T cells which are presented in higher number in theirs Peyer patches.